Preparation and Characterization of Zeolite Membrane for Bioethanol Purification - Aprilina Purbasari; Titik Istirokhatun; Ariestya Meta Devi; Lulluil Mahsunnah; Heru Susanto (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2013)
The use of bioethanol as an alternative fuel with a purity of more than 99.5% wt has prompted research on bioethanol purification. One of the promising methods used for bioethanol purification is pervaporation membrane. This research is aimed to prepare and characterize zeolite membranes for pervaporation membrane. The membrane preparation consisted of two stages, namely support preparation and zeolite deposition on the support. In support preparation, α- alumina and kaolin with specific composition (50:30; 40:40; 50:30) was mixed with additives and water. After pugging and aging process, the mixture became paste and extruded into tubular shape. The tube was then calcined at temperature of 1250 °C for 3 hours. After that, zeolite 4A was deposited on the tubes using clear solution made of 10 %wt zeolite and 90 %wt water and heated at temperature of 80 °C for 3 hours. Furthermore, the resulting zeolite membranes was washed with deionized water for 5 minutes and dried in oven at temperature of 100 °C for 24 hours. Characterization of zeolite membranes included mechanical strength test, XRD, and SEM. In the mechanical strength test, the membrane sample with α- alumina:kaolin = 50:30 (membrane A) has the highest mechanical strength of 46.65 N/mm2. Result of XRD analysis for the membrane A indicated that mullite and corundum phases were formed, which mullite phase was more dominant. Meanwhile the result of SEM analysis shows that zeolite crystals have been formed and covered the pores support, but the deposition of zeolite has not been optimal yet. The performance examination for bioethanol purification showed that the membrane could increase the purity of bioethanol from 95% to 98.5% wt. © 2013 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)